2006
DOI: 10.1590/s0100-204x2006000300012
|View full text |Cite
|
Sign up to set email alerts
|

Força iônica da solução de equilíbrio na adsorção de arsênio em latossolos brasileiros

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da força iônica da solução de equilíbrio sobre a adsorção e dessorção de arsênio, em 17 latossolos, de diferentes regiões geográficas brasileiras. A adsorção de As foi avaliada em dois valores de força iônica (15 e 150 mmol L -1 ), duas doses de As (15 e 150 µmol L -1 ), relação solo:solução final de 1:100 e pH 5,5. Não houve diferença nas porcentagens de adsorção, entre os valores de força iônica 15 e 150 mmol L -1 (63,51 e 64,46%). A porcentagem de desso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…Esses Latossolos já foram alvo de outros estudos de adsorção (Guilherme et al, 1998;Pierangeli et al, 2001aPierangeli et al, ,b,c, 2003Pierangeli et al, , 2004Campos et al, 2006), de teores semitotais de Ets (Campos et al, 2003), entre outros. A caracterização física, química e mineralógica desses solos pode ser encontrada em Silva et al (1996) e Silva (1997.…”
Section: Methodsunclassified
“…Esses Latossolos já foram alvo de outros estudos de adsorção (Guilherme et al, 1998;Pierangeli et al, 2001aPierangeli et al, ,b,c, 2003Pierangeli et al, , 2004Campos et al, 2006), de teores semitotais de Ets (Campos et al, 2003), entre outros. A caracterização física, química e mineralógica desses solos pode ser encontrada em Silva et al (1996) e Silva (1997.…”
Section: Methodsunclassified
“…Then, the samples were centrifuged for 20 min at 3000 rpm and the supernatant was collected for As analyses in order to calculate As adsorption. This batch configuration (methodology) used in this work has been documented in several studies involving metal adsorption and desorption [21][22][23][24][25][26]. The reaction time of 72 h was selected based on kinetic studies conducted on Oxisols (oxide-rich soils, as is the red mud), which showed that the reaction time used in this study (72 h) was sufficient to reach the equilibrium of the reaction between the solid and liquid phases [27].…”
Section: Arsenic Adsorption and Desorptionmentioning
confidence: 99%
“…In Brazil, gold and iron mining has contributed to the dispersion of As and its entry in the food chain (Campos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%